Renewable energy potential towards attainment of net-zero energy buildings status – A critical review. (15th June 2023) - Christopher, S.; Vikram, M.P.; Bakli, Chirodeep; Thakur, Amrit Kumar; Ma, Y.; Ma, Zhenjun; Xu, Huijin; Cuce, Pinar Mert; Cuce, Erdem; Singh, Punit
Abstract: Global warming, climate change, and resource depletion have forced us to reconsider energy usage and efficiencies over the last few decades. Residential and commercial buildings are both large energy consumers, so improving energy and material usage efficiency in this sector is a common research topic. According to a recent study, the Building Sector (BS) accounts for 40% of greenhouse gas emissions. The primary objective of this paper is to examine and assess the potential of Renewable Energy Systems (RES) and their combinations for enhancing energy efficiency in the BS. Specifically, the focus will be on converting low energy-efficient buildings into highly efficient ones. The potential of the RES and their combinations for the BS is evaluated based on payback durations, energy generation, and reduction of CO2 emissions. The optimization flow charts for the RES, feasibility studies, commercialization road maps of energy storage systems and the necessity of control mechanisms for enhancing RES efficiency were discussed. Additionally, the technology drawbacks are discussed, along with various innovative techniques recommended to direct future study in this area. Finally, this article assists the audience clear idea in the selection of the right combination of potential RES based on different conditions to achieve deep decarbonization in BSs. Highlights: Buildings sector (BS) responsible for 40% of GHG emissions. Study assesses potential of Renewable Energy System (RES) in BS. RES evaluated on payback, energy generation, and CO2 reduction. Optimization, feasibility and commercialization studies were discussed. Article recommends right RES combinations for deep decarbonization in BS.